Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd009729
|View full text |Cite
|
Sign up to set email alerts
|

Over the counter (OTC) artificial tear drops for dry eye syndrome

Abstract: Background-Over the counter (OTC) artificial tears historically have been the first line of treatment for dry eye syndrome and dry eye-related conditions like contact lens discomfort, yet currently we know little regarding the overall efficacy of individual, commercially available artificial tears. This review provides a much needed meta-analytical look at all randomized and quasi-randomized clinical trials that have analyzed head-to-head comparisons of OTC artificial tears.Objectives-To evaluate the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 35 publications
(56 reference statements)
0
36
0
3
Order By: Relevance
“…This is overwhelmingly fulfilled by topical therapies (see definition in table 2). Various studies and Cochrane SLRs support the daily use of topical therapies for the symptomatic relief of dryness, with a significant improvement in HRQoL without significant side effects 7 27 28. These therapies should be immediately initiated after objective confirmation of glandular dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is overwhelmingly fulfilled by topical therapies (see definition in table 2). Various studies and Cochrane SLRs support the daily use of topical therapies for the symptomatic relief of dryness, with a significant improvement in HRQoL without significant side effects 7 27 28. These therapies should be immediately initiated after objective confirmation of glandular dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…The first line of therapy for ocular dryness should be volume replacement and lubrication using artificial tears (AT) and ocular gels, whose main ingredients are lubricants with a polymeric base or viscosity agent (methylcellulose, hyaluronate) with the aim of adding volume to the tear lake, increasing the time the AT remain on the ocular surface, and cushioning the ocular surface to reduce friction between lid and globe 37. All SjS studies testing AT (only one in pSjS-2002 patients) found significant improvements for both subjective and objective ocular outcomes, while a recent Cochrane review on the use of AT for dry eye syndrome showed that they are safe and effective 28. We recommend that all SjS patients presenting with ocular dryness and/or abnormal ocular tests should use AT containing methylcellulose or hyaluronate at least twice daily, with the frequency increased to as often as hourly, as indicated by symptoms and/or objective signs.…”
Section: Resultsmentioning
confidence: 99%
“…We made this change because of the great variation in artificial tears found in the literature search. Our protocol did not include methods to prepare a “Summary of findings” table or assess the overall quality of evidence, as the protocol was published before this requirement was introduced (Pucker 2012). Although not specified in the protocol, we excluded studies in which the follow-up period was less than one week because our review aimed to investigate longer term outcomes.…”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…Last year a Cochrane Systematic Review found that most overthe-counter artificial tear preparations are similarly effective. 17 Some success has been achieved with antioxidants, and viscosity enhancers such as drops containing HPMC or hyaluronic acid are much used. Hypo-osmolar drops have been available for years and there is interest in newer osmoprotectants, including trehalose, a non-reducing sugar whose molecules cluster in aqueous solution.…”
Section: Dry Eye Disease Managementmentioning
confidence: 99%